Looking Within: A Call for Greater Reflexivity in Expatriate Research. (December 2022) - Ridgway, Alexandra; Lowe, Kate
Self-examinations of researcher positionality are central to understanding how scholars engage with research populations and vice versa. Discussions of how researchers are positioned are considered particularly important when studying groups whose vulnerability is well-accepted. Less is known, however, about the role of researcher positionality when interviewing participants deemed privileged, such as expatriates. Researchers who study expatriates overwhelmingly omit to discuss their positionality and how this shaped their research processes and outcomes. In response, our article calls for a turn in expatriate scholarship towards greater, and more public, examinations of researchers' social locations and their effects. Drawing upon our research experiences in Hong Kong, we explore the complexities of conducting reflective practice when investigating expatriate life and highlight an over-reliance on the field to trigger considerations of positionality. In response, we suggest that expatriate researchers should be more proactive in their reflexivity and offer some prompts for these self-assessments. Beyond this, we advocate for more conducive research environments, including systems of peer support, to enable expatriate researchers to deepen understandings of their own positionalities while also holding each other reflexively accountable. These suggestions also hold potential benefit for other sociologists such as those studying elite populations and/or the globally mobile.